2021
DOI: 10.1101/2021.08.03.21261482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reducing false reassurance following negative results from asymptomatic coronavirus (Covid-19) testing: an online experiment

Abstract: Objectives. Individuals who receive a negative lateral flow coronavirus (Covid-19) test result may misunderstand it as meaning no risk of infectiousness, giving false reassurance. This experiment tested the impact of adding information to negative test result messages about (a) residual risk and (b) need to continue protective behaviours. Design. 4 (residual risk) x 2 (post-test result behaviours) between-subjects design. Setting. Online. Participants. 1200 adults from a representative UK sample recruite… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Test result messages should communicate the residual risk of infection inherent in a negative test result and remind individuals of the importance of continuing to adhere to guidelines and engage in protective behaviours. 25 Importantly, some students noted that they or others may be less motivated to test during busy examination periods or after being vaccinated. Testing reminders should be sent during these busier periods and testing made as easy as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Test result messages should communicate the residual risk of infection inherent in a negative test result and remind individuals of the importance of continuing to adhere to guidelines and engage in protective behaviours. 25 Importantly, some students noted that they or others may be less motivated to test during busy examination periods or after being vaccinated. Testing reminders should be sent during these busier periods and testing made as easy as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Infographics continue to be studied across the world as a pandemic communication tool, with many current studies—some awaiting peer review—focused on the process of creating infographics [32] , [33] or their effects [34] , [35] , [36] . One study found newspaper infographics in India focused on risk information more than efficacy information [37] .…”
Section: Introductionmentioning
confidence: 99%